Comparison of automatic and CVT transmission for a car under 1 liter engine - Ahmad Mustakim, Mohd Rusli (2010)
This thesis presented about the comparison of automatic transmission and CVT transmission. Automatic transmission had been used widely nowadays and the use of CVT transmission progressively increasing. Automatic transmission and CVT transmission have their own advantages and disadvantages. In chapter 4, the performance of each transmission were analysed and the comparison between two transmissions in term of performance is different. Other than the performances, the transmissions also were differentiated in terms of fuel consumption and compatibility to build in a car under 1 litre engine. This performance is found by using calculation method and the results have been plot as a graph and